Studies on Susceptibility of Antibiotic Resistant Escherichia coli to Bacteriophages - S.S. Kachave; P.R. Suryawanshi; S.S. Gaikwad; G.R. Gangan; D.P. Patil; M.F.M. F. Siddique (The Indian Veterinary Journal, 2024)
Calf diarrhoea causes heavy economic losses to the dairy industry in the form of morbidity and mortality. In spite of advancement made in dairy husbandry practices, clinical medicine and diagnostic techniques, the morbidity and mortality rates of dairy calves are still unacceptably high worldwide. In this study 60 fecal samples were collected from calves for isolation and characterization of E. coli based on morphological and biochemical characteristics. Antibiotic sensitivity test of the obtained isolates (n=) was also performed. Bacteriophages were recovered from 40 sewage water and 20 fecal samples and were subjected to enrichment and efficacy of bacteriophage against antibiotic resistant E. coli. Antibiotic sensitivity test of E. coli isolates revealed multi drug resistant pattern of E. coli to most of the commonly used antimicrobials used on field for livestock treatment. It was observed that E. coli isolates were resistant to Ampicillin (96%), Tetracycline (85%), Oxytetracycline (81.66%), Cefotaxime (70%) and Nalidixic acid (66.66%). In this study 12 bacteriophages were isolated from the sewage and fecal samples. Out of which only 4 bacteriophages exhibited susceptibility against multidrug resistant bacterial isolates of E. coli isolated from calf feces. The selected E. coli were resistant to ampicillin and tetracycline. On assessing the host range and killing potential of newly isolated phages, it was found that all phages were narrow spectrum and found to be monovalent in nature. The finding that these bacteriophages were able to lyse E. coli species of bacteria indicated their high specificity for E. coli.